Constraining Southern Ocean CO2 Flux Uncertainty Using Uncrewed Surface Vehicle Observations. Issue 3 (9th February 2021) - Sutton, A. J.; Williams, N. L.; Tilbrook, B.
Abstract: Remote, harsh conditions of the Southern Ocean challenge our ability to observe the region's influence on the climate system. Southern Ocean air‐sea CO2 flux estimates have significant uncertainty due to the reliance on limited ship‐dependent observations in combination with satellite‐based and interpolated data products. We utilize a new approach, making direct measurements of air‐sea CO2, wind speed, and surface ocean properties on an Uncrewed Surface Vehicle (USV). In 2019, the USV completed the first autonomous circumnavigation of Antarctica providing hourly CO2 flux estimates. Using this unique data set to constrain potential error in different measurements and propagate those through the CO2 flux calculation, we find that different wind speed products and sampling frequencies have the largest impact on CO2 flux estimates with biases that range from −4% to +20%. These biases and poorly constrained interannual variability could account for discrepancies between different approaches to estimating Southern Ocean CO2 uptake. Plain Language Summary: The Southern Ocean is an important part of the global climate, playing an outsized role in the uptake of heat and carbon. Yet observing the Southern Ocean is challenging due to its size, remoteness, and harsh conditions. In 2019, we completed the first autonomous circumnavigation of Antarctica with an Uncrewed Surface Vehicle (USV), also known as an ocean robot, in order to address some of these observing challenges. By directly measuring air and surface seawater carbon dioxide (CO2 ) and wind speed on the USV, we were able to observe CO2 exchange between the ocean and atmosphere every hour during the mission. Using this data set, we estimated potential errors in these measurements as well as other approaches to estimating CO2 exchange. The use of different satellite‐based wind products and sampling frequency play the largest role in uncertainty of the uptake of CO2 in the Southern Ocean. In order to reduce this uncertainty and provide a better understanding of the Southern Ocean, expansion of an observing network made up of ships, USVs, and other autonomous devices is necessary. Key Points: The first autonomous circumnavigation of Antarctica allowed for direct measurements of air‐sea CO2 and wind speed in the Southern Ocean Bias and error propagation of various approaches to calculating CO2 flux could explain some of the discrepancies between previous estimates Interannual variability that is poorly constrained by observations are also likely contributing to the discrepancies in CO2 flux estimates